Reaction of the anammox granules to various antibiotics and operating the anammox coupled denitrifying reactor for oxytetracycline wastetwater treatment. (March 2022) - Wang, Shuailing; Li, Jun; Wang, ChangWen; Ma, Jing; Li, Zhe; Zheng, Zhaoming; Zhang, Jing
Graphical abstract: Highlights: The impact of different antibiotics against anammox granules was investigated. The Ki values of oxytetracycline and polymyxin sulfate were 188.5 and 17.7 mg/L. The short-run inhibition of penicillin upon anammox granules was negligible. Impact of oxytetracycline was studied in anammox coupled denitrifying reactor. Denitrifying bacteria had higher long-run tolerance than anammox bacteria. Abstract: The anaerobic ammonium oxidation (anammox) based technology has been considered as an economic and efficient way to remove nitrogen. However, the anammox bacteria could be strongly inhibited by antibiotics. In present research, inhibiting properties of oxytetracycline, penicillin and polymyxin sulfate upon the anammox activity were investigated through batch experiment. The results implied that anammox activity was significantly inhibited by oxytetracycline and polymyxin sulfate. The non-competitive inhibiting model showed that the inhibiting constants (Ki) of oxytetracycline and polymyxin sulfate were 188.5 and 17.7 mg/L, respectively. Meanwhile, the anammox process was not suppressed while the concentration of penicillin reached 3000 mg/L. In long-run experiment, the influent oxytetracycline concentration of the anammox coupled denitrifying reactor was operated at 20 mg/L. It was observed that the anammox performance completely deteriorated, while the NO2 – -N removing efficiency reached 15.8%. The obtained findings could provide important instruction for the treatment of antibiotic contaminated wastewater.